THE ROLE OF USER-GENERATED CONTENT AND DESTINATION VALUE PROPOSITION IN SHAPING TOURISTS’ VISIT INTENTION TO BANDA NEIRA: THE MEDIATING ROLE OF ATTITUDE - Nadya Nurlailya Ningsih; Feky Reken; Etvin Rizal Tamher (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the influence of user-generated content (UGC) and destination value proposition (DVP) on tourists’ visit intention to Banda Neira, Indonesia, with attitude serving as a mediating mechanism. Drawing on the Theory of Planned Behavior (TPB) and the Elaboration Likelihood Model (ELM), a quantitative research design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 200 potential tourists who had never visited Banda Neira but actively consume travel-related content on social media. Findings reveal that both UGC and DVP significantly and positively influence attitude toward the destination. In turn, attitude exerts a strong positive effect on visit intention. Mediation analysis confirms that attitude fully mediates the effect of UGC and predominantly mediates the effect of DVP on visit intention. The final model explains 49% of the variance in visit intention, highlighting the critical role of affective evaluation in digital destination marketing. Theoretical and practical implications are discussed, particularly for heritage destinations seeking to leverage digital storytelling and authentic value communication. Keyword: User-Generated content, destination value proposition, attitude, visit intention,heritage tourism